The Role of Language In Social Relations -The Field Of Administration As A Model - Badrkhan Suliman Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Language is one of the most basic necessities of life, in which all the various communications of human society are conducted and achieved through it. In other words, there will be no society without different forms of language since communications will not happen. Human beings use communication in different levels to facilitate their works and path of prosperity of life. Obviously, organizing and systematizing works in the society will require management in order to perform the duties properly whether on the level of the different administrative groups as it is expected and through a clear plan for serving various purposes (economical, political, financial, scientific and military…etc.) These reasons (The role of language in social relations (the field of administration as a model)) are the source and have led to conducting of this study, to demonstrate the role of language in administration, because in our view’s language went through the entire gaps of administration, in which the skill of using language will have a clear and outstanding reflection on affairs of administrative commands, since both of them (language and administration) are social phenomenon. The communication principle is the most important element and duty of both of Language and administration. Performing the successful communication, by taking advantage of (verbal and non-verbal) language leads to perform an effective administration and fostering a strong relationship between both human elements in administration that include managers and employees. In this research, after introducing administration and demonstrating its main duties, it illustrates communication; the types and styles of communication in the administration. Then, it elaborates) mainly on the directing as one of the duties of manager in administration, because the role of language will be appeared clearly in this duty of the administration. Afterwards, it has been clarified the types of leadership and the use of language differences in each type, in which when you can see the features of successful leaders in the managers, will be a charismatic person, of course this shows us that language has played a great role in this aspect.